"The False Appearance of Totality is Extinguished": Orson Welles's The Trial and Benjamin's Allegorical Image. Issue 1 (February 2019) - Koch, Julian
Abstract : This article seeks to renegotiate Walter Benjamin's conception of allegory as an image that is a "fragment [… in which] the false appearance of totality is extinguished" (1998, p. 176) in the context of Welles's The Trial. According to Benjamin, the allegorical image embodies its own limitations, displaying where its visuality falters. This article lifts Benjamin's notion of the allegorical image from its specific German Baroque discursive context and superimposes it onto the moving images of Welles's film. Welles's images in The Trial seem to perennially question their ability to meaningfully capture or represent the nature of the law. The faltering of the image is also apparent in Welles's use of cinematography, when offscreen space irrupts into Welles's images in unforeseeable ways, suggesting the powerlessness of the image over what is imposed upon it. In their displaying an absence of representation, Welles's images seem allegorical in Benjamin's sense.